(untitled) (BIRDEM Medical Journal, 2019)
Background: Quality of life (QOL) is one of the chief areas to be addressed when caring for people with end stage renal disease (ESRD). The continual excretory function of native kidneys are replaced in such patients by few hours of rapid urea clearance in a week. This study aimed to explore whether more weekly hemodialysis sessions and dialysis adequacy do actually improve parameters of QOL and if this is beneficial enough at the cost of taking additional dialysis sessions in a low income country like Bangladesh. Whether being diabetic influences QOL was also investigated. Methods: This cross-sectional study recruited 135 adults, who were on maintenance haemodialysis(MHD) for >3 months, from three dialysis centers in Dhaka from January to December, 2013. Patients with malignancy, dementia, and psychosis were excluded. Patients were interviewed once by the investigators to fill a validated Bangla version of the kidney disease quality of life short form questionnaire (KDQOL-SF-36 version 1.3) and calculate a QOL score. Results: Mean age, mean duration of chronic kidney disease (CKD) and MHD were 50±12 years, 4.9±5.1 years and 12±11.8 months respectively. Overall QOL score for the study sample was 50±17. Only 43(31.9%) patients received adequate hemodialysis (mean Kt/V=1.3) while the rest (with Kt/V<1.2) had achieved an average Kt/V of 0.8 (p<0.001). Duration of MHD, hemoglobin, serum albumin, and ferritin were not significantly different for those adequately dialysed, compared to the rest. Also no improvement in any QOL parameter was found in those with Kt/V>1.2 (adequate HD). However, when a comparison was made between those with 3 HD sessions/week (n=63, mean MHD duration 24±14 months) with patients receiving 2 HD sessions/week (n=72, mean MHD duration 8.4±11 months), the former group had lower “effect of kidney disease” scores (p=0.021), higher “quality of social interaction” scores (p=0.031) and lower “role emotion” scores (p=0.002). When diabetic patients (n=82, mean age 54±8 years, MHD duration 18.5±9.5 months) and non-diabetic subjects (n=53, aged 42±13 years, MHD duration of 25±16 months) were compared, “effects of kidney disease”, “cognitive function” and “quality of social interaction” scales were significantly higher in those having diabetes (with p<0.045, p<0.024 and p<0.022 respectively). Conclusion: Since achieving hemodialysis adequacy was not found to improve QOL scores, an additional dialysis session at extra cost every week may not be advisable for people of a low income country Birdem Med J 2019; 9(2): 138-146